The Impacts of School Climate and Teachers’ Teaching Experience on the Social Competency of State Junior High School Teachers - Lena Nofelia,; Jasrial, (Indonesian Research Journal in Education |IRJE|, 2024)
This research aimed to obtain data and information about the effect of school climate on the social competence of State Junior High School teachers in West Padang District, the effect of teacher teaching experience on the social competence of State Junior High School teachers in West Padang District, and the effect of school climate and teacher teaching experience on the social competence of State Junior High School teachers in West Padang District. It used correlational quantitative research with an associative type. The population was 124 Civil Servant teachers at State Junior High Schools in West Padang District, while the sample was 63 teachers. The research instrument used was a questionnaire with a Likert scale, which had five alternative answers. The data analysis showed a significant effect between school climate and teacher social competence at 58%, teacher teaching experience on teacher social competence at 35.4%, and school climate and teacher teaching experience together on teacher social competence at 62.8%.